Developmentally Regulated Innate Immune NFκB Signaling Mediates IL-1α Expression in the Perinatal Murine Lung - Butler, Brittany; De Dios, Robyn; Nguyen, Leanna; McKenna, Sarah; Ghosh, Sankar; Wright, Clyde J. (Frontiers in Immunology, 2019)
Bronchopulmonary dysplasia (BPD) is the most common morbidity complicating premature birth. Importantly, preclinical models have demonstrated that IL-1 receptor antagonism prevents the lung injury and subsequent abnormal development that typically results following perinatal exposure to inflammatory stresses. This receptor is activated by two pro-inflammatory cytokines, IL-1α and IL-1β. While many studies have linked IL-1β to BPD development, IL-1α is relatively under-studied. The objective of our study was to determine whether systemic inflammatory stress induces IL-1α expression in the neonatal lung, and if so, whether this expression is mediated by innate immune NFκB signaling. We found that endotoxemia induced IL-1α expression during the saccular stage of neonatal lung development and was not present in the other neonatal organs or the adult lung. This IL-1α expression was dependent upon sustained pulmonary NFκB activation, which was specific to the neonatal lung. Using in vivo and in vitro approaches, we found that pharmacologic and genetic inhibition of NFκB signaling attenuated IL-1α expression. These findings demonstrate that innate immune regulation of IL-1α expression is developmentally regulated and occurs via an NFκB dependent mechanism. Importantly, the specific role of developmentally regulated pulmonary IL-1α expression remains unknown. Future studies must determine the effect of attenuating innate immune IL-1α expression in the developing lung before adopting broad IL-1 receptor antagonism as an approach to prevent neonatal lung injury.